Laparoscopic pancreatic resection. From enucleation to pancreatoduodenectomy. 11-year experience - Machado, Marcel Autran Cesar (2013)
Context Our experience with laparoscopic pancreatic resection began in 2001. During initial experience, laparoscopy was reserved for selected cases. With increasing experience more complex laparoscopic procedures such as central pancreatectomy and pancreatoduodenectomies were performed. Objectives The aim of this paper is to review our personal experience with laparoscopic pancreatic resection over 11-year period. Methods All patients who underwent laparoscopic pancreatic resection from 2001 through 2012 were reviewed. Preoperative data included age, gender, and indication for surgery. Intraoperative variables included operative time, bleeding, blood transfusion. Diagnosis, tumor size, margin status were determined from final pathology reports. Results Since 2001, 96 patients underwent laparoscopic pancreatectomy. Median age was 55 years old. 60 patients were female and 36 male. Of these, 88 (91.6%) were performed totally laparoscopic; 4 (4.2%) needed hand-assistance, 1 robotic assistance. Three patients were converted. Four patients needed blood transfusion. Operative time varied according type of operation. Mortality was nil but morbidity was high, mainly due to pancreatic fistula (28.1%). Sixty-one patients underwent distal pancreatectomy, 18 underwent pancreatic enucleation, 7 pylorus-preserving pancreatoduodenectomies, 5 uncinate process resection, 3 central and 2 total pancreatectomies. Conclusions Laparoscopic resection of the pancreas is a reality. Pancreas sparing techniques, such as enucleation, resection of uncinate process and central pancreatectomy, should be used to avoid exocrine and/or endocrine insufficiency that could be detrimental to the patient's quality of life. Laparoscopic pancreatoduodenectomy is a safe operation but should be performed in specialized centers by highly skilled laparoscopic surgeons.